PENERAPAN MODEL PEMBELAJARAN STUDENT CENTERED LEARNING (SCL) DI FAKULTAS KEPERAWATAN UNIVERSITAS JEMBER - Ilhami, Ridlo Cahya; Purwandari, Retno; Afandi, Alfid Tri (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Learning process in university must be conducted with the principle of Student Centered Learning (SCL). SCLhas several components that could influence the implementation of SCL. The purpose of this study was toidentify the implementation of SCL in Nursing Faculty of Jember University. This study used a descriptiveexploratory design with purposive sampling technique on 26 lecturers and stratified sampling techniques for 260students. The results showed that the implementation of SCL to lecturers reached 81.7% (from a maximum valueof 33) and the implementation of SCL to students reached 80.19% (from a maximum of 36). This shows theimplementation of SCL in terms of students and lecturers having a good score. The lowest score for lecturerswas the class condition (68.4%) and the lowest value for students was the teaching material (71%). Lack offacilities could have an impact on the disruption of the learning process using SCL so that students and lecturersdid not get maximum results. Institutions are expected to be able to renew their collection of books and classconditions can be further optimized by reducing the number of students to 25 students in each class.